Participatory budgeting for results and decision-making in Chiclayo municipalities - Urbina Cárdenas , Max Fernando; Chanduví Calderón , Roger Fernando; Zuloeta Salazar , José Félix; Chapoñan Ramírez , Edgard; Balcázar Paiva , Eveling Sussety (Journal of the University of Zulia, 2021)
The purpose of this study was to establish the level of relationship between participatory budgeting by results and decision-making in the assignment and execution of projects of the municipalities of the province of Chiclayo, 2019. The research was descriptive and correlational. The sample was made up of the residents of four most significant district municipalities in the province of Chiclayo: Chiclayo, La Victoria, José Leonardo Ortiz and Pimentel. The technique used to collect the information was the survey; and the instrument, the questionnaire for the evaluation of the participatory budget and decision-making. Descriptive analysis and inferential analysis were carried out to test the research hypothesis, using Pearson's statistical correlation technique. The results found indicate that there is a correlation between participatory budgeting and decision making. In conclusion, the decision-making that is carried out for the execution of the works will be efficient, once the participatory budget is conceived and applied as an instrument of efficient policy and management, through which the regional and local authorities, and the Duly represented population organizations define a set of duly planned actions, in order to direct the resources of said budget.